Chronic intestinal pseudo-obstruction in systemic lupus erythematosus. Issue 1 (1st July 1998) - Perlemuter, G; Chaussade, S; Wechsler, B; Cacoub, P; Dapoigny, M; Kahan, A; Godeau, P; Couturier, D
Abstract : Background/Aims —Chronic intestinal pseudo-obstruction (CIPO) reflects a dysfunction of the visceral smooth muscle or the enteric nervous system. Gastrointestinal manifestations are common in systemic lupus erythematosus (SLE) but CIPO has not been reported. Features of CIPO are reported in five patients with SLE. Methods —From 1988 to 1993, five patients with SLE or SLE-like syndrome were hospitalised for gastrointestinal manometric studies. CIPO was the onset feature in two cases. Antroduodenal manometry (three hours fasting, two hours fed) was performed in all patients, and oesophageal manometry in four. Results —Intestinal hypomotility associated with reduced bladder capacity and bilateral ureteral distension was found in four patients and aperistalsis of the oesophagus in three. Treatment, which consisted of high dose corticosteroids, parenteral nutrition, promotility agents, and antibiotics, led to remission of both CIPO and urinary abnormalities in all cases. Antroduodenal manometry performed in two patients after remission showed increased intestinal motility. One patient died, and postmortem examination showed intestinal vasculitis. Conclusions —CIPO in SLE is a life threatening situation that can be reversed by treatment. It may be: ( a ) a complication or onset feature of the disease; ( b ) secondary to smooth muscle involvement; ( c ) associated with ureteral and vesical involvement; ( d ) the result of intestinal vasculitis.